Real exchange rate in Ecuador: Decomposition and misalignment with the real equilibrium exchange rate - ESPIN, STEPHANIE (2021)
The objective of this research is the analysis of the Ecuadorian Real Exchange Rate Index (ITCR) considering two angles. The first, to investigate the evolution of the variable through the factors that intervene in its calculation: the nominal exchange rate and relative prices. The second, to quantify the misalignment of the ITCR from its equilibrium path (TCRE). The analysis period runs from 2003 to the first half of 2021. The estimation of the TCRE is made applying the BEER methodology. The variables included are the terms of trade (TI), government spending, productivity, remittances, trade openness (CA) and net external assets (AEN). In conclusion, the greatest undervaluation of the ITCR occurred from 2003 until before the financial crisis of 2009, a period in which the ITCR had a marked period of depreciation mainly explained by the nominal exchange rate. On the other hand, the period of greatest overvaluation of the ITCR occurred following the shock experienced by the country due to the decrease in the international price of raw materials in 2014. The fundamental that most strongly influences the evolution of the TCRE is trade openness.